Assessment of the mechanical and environmental behavior of diesel engines operating with biodiesel mixtures - César Fabricio Morales-Bayetero; Edilberto Antonio Llanes-Cedeño; Carlos Mafla-Yépez; Alberto Rodríguez-Rodríguez (Revista Facultad de Ingeniería Universidad de Antioquia, 2023)
Biodiesel is one of the best renewable fuels to reduce dependence on petroleum derivatives. The objective of this work is to evaluate the mechanical and environmental performance in compression ignition engines with the use of biodiesel in proportions of 5 % (B5), 15 % (B15), and mixtures with additive B5A and B15A, through the experimentation and use of automotive measuring equipment, for mass application in automotive vehicles. The methodology applied is based on the development of two stages; the first is the preparation of the mixtures to be used in the research with the corresponding diesel/biodiesel percentage for each, and the second is the analysis of mechanical and environmental behavior through the use of properly calibrated and updated diagnostic equipment. The results show that the B5 mixture shows the best values, managing to maintain power and torque with non-significant decreases compared to diesel, with averages of 1.1 % and 0.3 %, respectively. As the percentage of biodiesel increases, the opacity value decreases from 44.8 % with B15 and 59.3 % with B15A. In relation to exhaust gases, additive mixtures show the most significant reduction in CO2, CO, and HC emissions, while NOx emissions rise slightly as biodiesel concentration increases, but statistically, it is not significant.